FXR activation reduces the formation of macrophage foam cells and atherosclerotic plaque, possibly by down regulating hepatic lipase in macrophages - Qiang Gu; Jia Liu; Li Li Shen (FEBS Open Bio)
Macrophages are the most important immune cells affecting the formation of atherosclerotic plaque. Nevertheless, the mechanisms that promote formation of foamy macrophages during atherogenesis remain poorly understood. This study explored the effects of Farnesoid X receptor (FXR) and hepatic lipase (HL, encoded by LIPC) on atherogenesis, particularly in foamy macrophage formation. A luciferase reporter assay indicated that FXR could bind to the LIPC promoter and inhibit LIPC transcription. FXR agonist GW4064 decreased HL expression, foam cell formation, and increased the expression of FXR downstream genes and polarization to M2 in ox‐LDL‐induced THP‐1 and U937 foam cells. In addition, GW4064 exerted anti‐atherosclerotic effects in ApoE−/− mice, manifested as decreased serum cholesterol and triglyceride levels, and alleviated atherosclerotic plaque formation. Collectively, FXR exerted anti‐atherosclerotic effects, possibly by negatively regulating HL expression in macrophages.